Abgrenzung deutscher Arbeitsmarktregionen - Hans-Friedrich Eckey; Reinhold Kosfeld; Matthias Türck (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2006)
Functional delineated labour market regions are needed for regional economic analyses. In dependence of the definition of regions economic regions in space can be seen as rich or poor areas. In addition to this statistical and econometric reasons argue for using functional labour market regions. The available definitions of functional units are based mostly on data from 1980s and 1990s. To that extent a new delineation is required. We use a factor analysis with an oblique rotation and receive 150 labour market regions, which consist of one or more administrative units (Kreise). These labour markets regions fulfil the criterion of reasonable commuting time (maximally 45 to 60 minutes in dependence of the attractiveness of the centre). They have a size of more than 50,000 inhabitants.
Keywords: C21; R11; R58; 330; Labour Market Regions; Factor Analysis; Germany; Regionaler Arbeitsmarkt; Räumliche Verteilung; Deutschland; Schleswig-Holstein; Hamburg (Region)